Association Between Cancer Prevalence and Different Socioeconomic Strata in the US: The National Health and Nutrition Examination Survey, 1999–2018 - Wang, Mingsi; Liu, Yang; Ma, Yi; Li, Yue; Sun, Chengyao; Cheng, Yi; Cheng, Pengxin; Liu, Guoxiang; Zhang, Xin (Frontiers in Public Health, 2022)
Background: Inequality in health outcomes in relation to Americans’ socioeconomic status is rising. American Cancer Society depicts the most common cancers diagnosed in men and women in 2021. We aim to study socioeconomic inequalities in related cancers to investigate whether the cancer prevalence differs within family income to poverty ratio (PIR). Methods: The study examined data from adults aged 20 to 85 years participating in the 1999–2018 National Health and Nutrition Examination Survey (NHANES) who had complete data available on PIR and cancer or malignancy information (n=49,720). Participants were stratified into 3 categories of PIR: high income (PIR ≥ 4), middle income (> 1 and <4), or at or below the federal poverty level (≤ 1). Results: The prevalence of prostate cancer was higher in middle (3.61% [n= 464]) and high-income group (3.36% [n= 227]) than in low-income group (1.83% [n= 84], all p <0.001). The prevalence of breast cancer was higher in middle (2.86% [n= 390]) and high-income participants (3.48% [n= 218] ) than in low-income participants (2.00% [n= 117], all p <0.001). Compared with low-income group in men (0.48% [n= 22]), a higher prevalence of colon and rectum cancer occurs in middle-income (0.87% [n= 112], p =0.012) and high-income group (0.89% [n= 58], p =0.018). The prevalence of lung cancer of women was lower in high-income participants than middle-income participants (0.10% [n= 6] vs 0.29% [n= 39], p =0.014). Conclusions: Increasing disparities of cancer prevalence were identified across all socioeconomic categories analyzed in this study. To ensure sustainable global development, increased efforts are needed to reduce these health inequalities. To ensure the sustainable development goals, it is a global health priority to understand inequalities in health, and to target interventions accordingly.